2013
DOI: 10.5120/13854-1715
|View full text |Cite
|
Sign up to set email alerts
|

Texture based Emotion Recognition from Facial Expressions using Support Vector Machine

Abstract: The mission of automatically recognizing different facial expressions in human-computer environment is significant and challenging. This paper presents a method to identify the facial expressions by processing images taken from Facial Expression Database. The approach for emotion recognition is based on the texture features extracted from the gray-level co-occurrence matrix(GLCM) . The results show that the features are highly efficient to discriminate the expressions and require less computation time. The ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Statistical and features that are taken from GLPM are given as the input for classification to SVM. The detection rate is identified as 90% [4]. The algorithm detects the characteristic points of a victimization abstraction filter technique by the data given by author [5].…”
Section: Texture-basedmentioning
confidence: 99%
“…Statistical and features that are taken from GLPM are given as the input for classification to SVM. The detection rate is identified as 90% [4]. The algorithm detects the characteristic points of a victimization abstraction filter technique by the data given by author [5].…”
Section: Texture-basedmentioning
confidence: 99%
“…In this section, we have elaborated on few research articles which detects human facial expressions. Punitha et al [20] proposed a technique to recognise the facial expressions using texture information on face and trained the texture features with support vector machine (SVM) to classify the facial expressions. Schiavenato et al [21] study contributes pain recognition in the RGB video of infants using computer enabled point pair and NFSC facial action methods.…”
Section: Facial Expressions and Pain Recognitionmentioning
confidence: 99%
“…Punitha et al . [20] proposed a technique to recognise the facial expressions using texture information on face and trained the texture features with support vector machine (SVM) to classify the facial expressions. Schiavenato et al .…”
Section: Facial Expressions and Pain Recognitionmentioning
confidence: 99%
“…Data on the direction of a data point , the larger the values of x shows a corresponding increase on the Gram Matrix . Studies have shown polynomial kernels have been applied to overcome challenges in various fields, such as person re-identification problem by correctly matching person image from a set of gallery of person images in the field of machine learning [ 21 ], new malware detection in cyber-security [ 22 ], big data classification [ 23 ], facial recognition on multiple face images [ 24 ], human body movement and posture recognition in the medical field [ 25 ], facial emotion recognition [ 26 ] and classification of human brain images against mental health conditions in medical imaging [ 27 ]. Radial Basic Function (RBF Kernel), also known as the Gaussian Similarity Kernel defined as .…”
Section: Related Workmentioning
confidence: 99%